Environmentally Benign Syntheses and Characterization of 4- Aryldihydropyrimidin-2(1H)-ones - Syed Salman, Shafqat; Amir Azam, Khan; Misbahulain, Khan; Kuan, Nicholas Hoo Tien; Mohd Syahmi, Jamaludin; Pang, Suh Cem (EDP Sciences, 2016)
A general, simple, efficient, cost-effective and environmental benign procedure for the syntheses of 4-aryl-3,4-dihydropyrimidin-2(1H)-ones (DHPMs) has been developed. The reaction is efficiently catalysed by using various amino acids viz., glycine, L-proline, L-cysteine, leucine and tryptophan. Reactions give excellent yields under reflux conditions. The chemical structures of these compounds were identified by Fourier Transform-Infra Red Spectroscopy (FT-IR), Gas Chromatography-Mass Spectroscopy (GC-MS) and Nuclear Magnetic Resonance Spectroscopy (1H NMR). Physical parameters such as m.p., mixed m.p. as well as TLC also helped to characterize the expected products. The progress of the reaction time and purity was checked by TLC and the products were purified by recrystallization using ethyl acetate as a solvent. The synthesized molecule has numerous biological applications as it is anti-microbial, anti-inflammatory and anti-hypertensive in character